Melons of Uzbekistan - Mavlyanova, R.; Rustamov, A.; Khakimov, R.; Khakimov, A.; Turdieva, M.K.; Padulosi, S. (2005)
Trilingual publication: English, Russian and Uzbek In the year 2000, during the scientific expedition by the Uzbek Research Institute of Plant Industry (UzRIPI) under support of the International Plant Genetic Resources Institute (IPGRI), melon-growing areas of Uzbekistan were surveyed, farmers' plots were studied, and the melon varieties grown were described and collected. This survey mission has been conducted within the framework of the project ”Enhancement of the use of melon genetic resources in Uzbekistan through the strengthening of on farm and ex-situ conservation” under the leadership of Dr. S. Padulosi and Ms. M.K. Turdieva from the IPGRI Regional office.The book of ”Melons of Uzbekistan”, is written on the basis of this mission's results. The book includes expanded data on varietal distribution in melon growing areas, detailed descriptions of old local melon varieties under cultivation, new forms, and breeding melon cultivars developed over the last forty years along with literature references. The publication is intended for scientists, agronomists, students, and the public at large.